Interactive craft activities – elevating special needs education learning tools with Craft Interactive Teaching Approach / Siti Zuraida Maaruf, Nurul Syawani and Tamil Selvan Subramaniam - Maaruf, Siti Zuraida; Syawani, Nurul; Subramaniam, Tamil Selvan (Universiti Teknologi MARA, 2021)
The aim of this study is to determine the Expert Panels agreement and consensus on the suitable items for the development of the Craft Interactive Teaching Approach (CiTA). A purposive sampling consisting of 12 Expert Teachers with more than ten years of experience in the field of Special Education were used in this research to measure their consensus on the design and development of the CiTA video module. The CiTA video module was developed using the ADDIE Model that is supported by the Delphi Technique. This study utilised the Design Development Research (DDR) approach that consisted of three phases. However, for the purpose of this article, the researchers will only discuss Phase 2: Design and Development in developing the Interactive Teaching Approach Video module. The responding twelve VAE teachers provided positive feedback towards learning and teaching using the tutorial module. With the interquartile range of 0 to 1.00 for all items included in the activities, all Expert Teachers in the field of Special Education approved with the content of the CiTA video module from the two rounds of Delphi surveys performed. The CiTA video module was developed with the inclusion of all items that were highly approved by the participating Expert Teachers in the Special Needs Education. Since the two rounds of item evaluation demonstrated a significant relationship between Round One and Round Two, the development of the video module could improve inclusive learning in the Malaysian classroom.